PENGARUH PEMBERIAN PENGHARGAAN DAN SANKSI TERHADAP KINERJA PEGAWAI - Endi Mulyadi (Jurnal Tata Kelola Pendidikan, 2021)
This research entitled "The Effect of Rewards and Sanctions on Employee Performance in the Center for Development and Empowerment of Educators and Education Personnel in the Field of Mechanical and Industrial Engineering (PPPPTK BMTI) Cimahi City". In this research, the method used is quantitative method. The sampling technique used in this research is probability sampling, which is a sampling technique that provides equal opportunities for each element (member) of the population to be selected as a member of the sample. Based on data processing carried out by calculating the WMS (Weight Means Score), it shows the average general tendency for reward and sanctions variables and employee performance variables to be in good category. The results of the analysis of the correlation coefficient between variable X and variable Y obtained a positive result of 0.539 which indicates that variable X and variable Y have a "strong" relationship. The results of the significance test for the correlation coefficient indicate that with the test rules tcount ttable 5.116 1.998. So Ha accepted. Then in the analysis results the coefficient of determination variable X contributes to variable Y by 29% while the other 71% is found in other factors. Then the results of a simple regression analysis show 22.605 + (0.539) X, if the rewards and sanctions (X) increase, the employee performance (Y) will increase by 0.539. This means that if the rewards and sanctions increase by 0.539, the employee's performance will increase by 0.539. The conclusion of this study is rewards and sanctions and employee performance have a positive influence with the category of strong relationship strength. This positive relationship indicates that the increasing rewards and sanctions will have an effect on improving employee performance.